Cardiac MRI-detected acute myocardial infarction without coronary obstruction caused by embolism in an atrial fibrillation patient: A case report - Nabil Laktib; Selma Saidi; Hicham Faliouni; Ilyasse Asfalou; Aatif Benyass; Zouhair Lakhal (Radiology Case Reports)
Myocardial Infarction with No Obstructive Coronary Arteries (MINOCA) accounts for up to 12% of acute coronary syndromes. Among its various causes, coronary embolism remains an uncommon yet often overlooked cause. Compared to other causes of myocardial infarction, coronary embolism can result in more severe outcomes, making its early recognition and management crucial. We report the case of a 62-year-old female patient with a history of atrial fibrillation, who was admitted for a myocardial infarction with no coronary obstruction. Paraclinical evaluations confirmed myocardial necrosis, but no thrombus was visible on coronary angiography. Despite the patient's low adherence to therapy, anticoagulation treatment led to thrombus resolution prior to performing coronary angiography. This case highlights the critical role of clinical context and cardiac magnetic resonance in diagnosing coronary embolism, particularly in the setting of MINOCA. It also underscores the potential impact of low anticoagulation adherence, which may contribute to coronary embolism despite the absence of visible obstruction on coronary angiography.